American experience. The eugenics crusade [videorecording (DVD)] : what's wrong with perfect? - Stoll, Corey, 1976- (PBS, 2018)
It tells the story of the eugenics movement and its long history in the United States, from its beginnings in the study of heredity to its rise as a popular movement promising to uplift the human race through state-sponsored sterilization, to its influence on immigration laws designed to close our borders to groups deemed genetically inferior.